Expanded Blast Design For Tight Controlled Hard Rock Trenching Adjacent To Twin Burried Live Oil Pipelines - A. Ravi Kumar (International Society of Explosives Engineers, 2008)
A trench is a structure to accommodate fluid carrying pipelines for water, gas, petroleum products etc. Trench serves the purpose to haul the fluids in bulk over long distances safely and economically. Use of pipeline for moving oil and gas was essentially a post World War II development, but now it has acquired its own importance.